Barriers to employment as experienced by disabled university graduates in Yogyakarta, Indonesia. Issue 2 (25th March 2021) - Lessy, Zulkipli; Kailani, Najib; Jahidin, Asep
Abstract: Because of experiencing discrimination, denial, stress, and rejection from prospective employers, disabled university graduates struggle to find jobs. By interviewing eight participants and conducting a focus group discussion with them at Sunan Kalijaga State Islamic University Yogyakarta, the findings revealed that the teaching procedures in larger inclusive classrooms seemed to be a barrier for most disabled university students. Consequently, the students needed vocational training in addition to their courses before integrating into the workforce. Recalling when being students, these disabled university graduates found it difficult to prepare for jobs that required math or science because their university courses had not included assistance with different kinds of media. Additionally, they did not feel prepared for writing curriculum vitae and preparing job applications. They indicated that the university setting did not prepare them to deal with the typically fierce competition in job markets. They also found getting a job in the labor market to be difficult because a scarcity of formal employment opportunities suitable to their fields, and employers do not provide feedback or even any reply at all, to their job applications. In summary, academic, social, cultural, economic, psychological barriers, and discriminatory practices were encountered for disabled university graduates seeking employment.